Créditos - Llamas Martínez, Jacobo (Lectura y signo, 2023)
<span style="caret-color: rgba(0, 0, 0, 0.87); color: rgba(0, 0, 0, 0.87); font-family: 'Noto Sans', -apple-system, BlinkMacSystemFont, 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration: none; display: inline !important; float: none;">Créditos, agradecimientos y otras informaciones